Analisis Pemahaman dan Kesulitan Siswa pada Materi Kaidah Pencacahan di Kelas X SMA Negeri 1 Percut Sei Tua - Kairuddin Kairuddin; Novitasari Br Hutauruk; Yulita Rotua Putri S. Sihite; Esther Putri Veronica Siregar; Yehekiel Torino F Sinaga (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to identify the difficulties faced by tenth-grade students in understanding enumeration rules and to find effective learning solutions. The research method used was descriptive qualitative, with 33 tenth-grade students of SMA Negeri 1 Percut Sei Tuan as subjects. The instruments used included a diagnostic test in the form of National Examination questions 7-11 on permutations and combinations, interviews with mathematics teachers, and classroom observations. The results showed that the majority of students (50%) were in the moderate understanding category, understanding the basic concepts but frequently making procedural errors. Thirty percent of students were in the low understanding category, having difficulty distinguishing between addition and multiplication rules and applying the concepts to word problems. The main obstacles identified included a lack of mastery of basic concepts, difficulty determining solution steps, a lack of varied practice questions, and limited interactive learning media. Recommended solutions include the use of visual media such as tree diagrams and tables, a contextual approach to everyday life problems, collaborative learning, and the provision of additional tutoring.